PERANCANGAN KOMPLEK MASJID AL FURQAN DI BANJARMASIN - Yuliono, Eko Ade; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2023)
The mosque serves as the hub for all activities, particularly those that are religious and linked to prayer. When a mosque's current structure is unable to handle the activities of its congregation as a result of societal change and population growth, problems arise. Comfort in serving the congregation and the community supports the construction of ideal circumstances in a mosque. Planning functions and forms that make the most of current circumstances can facilitate easy accessibility and the requirements of the congregation's activities. Lastly, a mosque is a container or location that accommodates all activities linked to prayer and other religious activities. It is not only an identity or a symbol.